Effects of titration parameters on the synthesis of molybdenum oxides based catalyst - Suppiah, D.D; Hamid, F.A; Kutty, M.G; Abd. Hamid, S.B (Universiti Kebangsaan Malaysia, 2012)
Molybdenum oxides catalysts are extensively used in various selective oxidation reactions. In this work, controlled precipitation method was used to synthesise molybdenum oxides. The effects of various titration parameters on the precipitate growth rate and structure throughout catalyst synthesis were investigated. The titration parameters varied for this study were molybdates (ammonium heptamolybdate) concentration, precipitation agent (HNO3) concentration, precipitating agent rate of addition and temperature of synthesis. X-Ray diffraction (XRD) and Field Emission Scanning Electron Microscope (FESEM) were used to characterize the catalysts. This study highlights the significant effects of the titration parameters varied on the supersaturation of the solution therefore yielding precipitate with different morphology. It was observed that the temperature played the major role followed by molybdate concentration in the formation of the bulk catalyst. Supramolecular structure (Mo36O112) was observed at lower temperature (30ºC) and lower molybdate concentration (0.07 M, 0.10 M) while at higher temperature (50ºC) and higher molybdate concentration(0.14 M) hexagonal (h-MoO3) phase structure was formed. Fast rate of addition and high concentration of precipitating agent affected the solution equilibrium leading to unclear inflection point (supersaturation point) at the titration curve.